Does State Tightness-Looseness Predict Behavior and Attitudes Early in the COVID-19 Pandemic in the USA?. (June 2022) - Gilliam, Ashley; Schwartz, Danielle B.; Godoy, Ricardo; Boduroglu, Aysecan; Gutchess, Angela
We investigated how tightness-looseness, reflecting strictness of social norms, of state of residence in the USA predicts behaviors and attitudes related to COVID-19. Because individual-level tightness may better capture current attitudes during the pandemic, whereas state-level archival measures reflect historical factors, we assessed the extent to which tightness-looseness at both levels predicted adherence to public health guidelines and biases toward outgroups related to COVID-19. In Spring 2020, 544 mTurk participants, primarily from the 13 tightest and 13 loosest states, completed survey questions about health behaviors in response to COVID-19, endorsement of future policy changes, feeling of responsibility for lives, and attitudes toward groups marginalized during the pandemic (i.e., Asians, older adults). State-level results indicated some associations with attitudes toward Asians and older adults, but effects were not robust. Results based on individuals' ratings of the tightness of their state indicated that higher levels of perceived tightness were associated with higher levels of protective self-reported public health behaviors (e.g., mask wearing, handwashing) during COVID-19, more endorsement of future policy changes to contain the pandemic, higher reported feelings of responsibility for one's life, and stronger negative attitudes toward Asians. The relations between tightness and health outcomes persisted after controlling for political attitudes and demographics. Thus, individual, more than state, tightness-looseness accounted for some degree of public health behaviors (unique contribution of individual tightness: R 2 = .034) and attitudes toward marginalized groups ( R 2 = .020) early during the COVID-19 pandemic. The implications of these findings for interventions to support behavior change or combat anti-Asian bias are discussed.